Buurtzorg: the district nurses who want to be superfluous. (6th July 2017) - Sheldon, Tony
Abstract : A Dutch model of coordinating care at home for elderly and vulnerable people could revolutionise healthcare, commentators effuse. Tony Sheldon asks whether Buurtzorg lives up to the hype